Persepsi Masyarakat Terhadap Pembangunan Kampus Politeknik Pariwisata Negeri Lombok - Abdurrahman Abdurrahman; Ramayanto Ramayanto; Ayu Suasmy (JIAP (Jurnal Ilmu Administrasi Publik), 2018)
The Public Perception of the Construction of Lombok State Tourism Polytechnic Campus, the researchers concluded that the construction of campuses especially in Puyung Village is very important and needs to be developed so that the potential and interest of residents to continue their education to a higher level as concluded from the interviews stated that the majority of education in Puyung Village is a high school level of 50%. The Regional Government and Puyung Village must solve the problems currently being faced so that the campus construction runs smoothly so that there are no more problems. The research methodology used is descriptive qualitative research methodology. The results showed that around 58% of the community of Puyung Village agreed to the construction of the campus and about 42% of the people of Puyung Village did not approve of the development of the Polytechnic Lombok campus. The campus construction had enormous benefits for the people of Puyung Village. The perception of the community of Puyung Village that approved the construction of the campus hopes to reduce the number of unemployed people in the surrounding area and can increase Human Resources (HR) in the economic field.